Bridging Knowledge, Protection and Development Gaps Through an Interdisciplinary Multi-Stakeholder Approach to Natural Hazards Risk Management - Nadia Netti; Martina de Cristofaro (Businesses)
The escalation of climate-induced disasters underscores how climatic variability has become a main question in designing risk-sensitive policies in advanced and developing countries. The macroeconomic implications of Natural Hazards (NHs) are extremely significant, as they can compromise financial stability and long-term prosperity. To mitigate risks and close the knowledge, protection, and development gaps can free resources, speeding up reconstruction of infrastructure, recovering from disruption of supply chains, and returning to pre-disaster levels of activities. This is not a simple task involving different steps of a “ladder approach”, sharing the burden of cost and responsibilities across the relevant stakeholders and reducing moral hazard. This approach rests on Public–Private Partnerships (PPPs) and technological R&D public investments able to crowd private ones in and establish useful Public–Private Insurance Schemes enhancing the disaster risk management role of the state. This paper proposes leveraging innovation technology both to enhance risk assessment and reduce uncertainty for climate-related NHs such as landslides. It is an important interdisciplinary question; in fact, despite the unequivocal acknowledgment of the global warming system, the precise ramifications of global warming and associated climatic shifts on NHs like landslides remain still elusive. The advanced modeling technique implemented by our interdisciplinary PPP contributes to geographically circumscribe the areas eventually subjected to landslides and constantly monitor the vulnerability of their structures, infrastructures, economic activities, and hence population. The reliable data that we can produce through remote sensing acquisition systems are necessary inputs to contain risk exposure both physically and financially.